Planning System Si-GIIS (Goods Inventory Information System) - Dewi Rahmasari; Feri Nugroho; Anindya Ananda Hapsari; Untung Suprihadi; Muhamad Aldiansyah; Safira Faizah; Nurul Aslamiah Istiqomahi (Jurnal Informatika Universitas Pamulang, 2021)
Web-based information technology is currently developing very rapidly. The utilization of web-based information technology is widely used in various types of work. One of them is the processing of inventory data. Talenta Store is a store engaged in the sale of mobile phone accessories. The management of inventory at Talenta Store is still not systematized. So that making inventory data with sales often makes mistakes and also owners sometimes find reports that are not appropriate. Therefore, a system that can support inventory data processing activities is made, namely the system Si-GIIS (Goods Inventory Information System) web-based. The development Si-GIIS system uses the FIFO (First in First Out) method design, which means that the goods purchased first will be sold first as inventory management. Si-GIIS was developed using the waterfall method and for system design using UML (Unified Modeling Language). n the test, Si-GIIS uses BlackBox testing with the final result that all systems work as expected. From the results of the satisfaction survey, it can be seen that 93% of employees and shop owners are very satisfied. Therefore, the development of the Si-GIIS system at the Talenta Store can be said to be successful and can be implemented into the inventory data processing system.